2020
DOI: 10.1002/jbmr.4539
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Metastatic Bone Lesion Type and Tumor Origin on Human Vertebral Bone Architecture, Matrix Quality, and Mechanical Properties

Abstract: Metastatic spine disease is incurable, causing increased vertebral fracture risk and severe patient morbidity. Here, we demonstrate that osteolytic, osteosclerotic, and mixed bone metastasis uniquely modify human vertebral bone architecture and quality, affecting vertebral strength and stiffness. Multivariable analysis showed bone metastasis type dominates vertebral strength and stiffness changes, with neither age nor gender having an independent effect. In osteolytic vertebrae, bone architecture rarefaction, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Research into bone quality under the purview of reference 29 has demonstrated that bone metastasis from prostate and breast cancers significantly affects bone quality. This study identifies notable reductions in vertebral strength and stiffness under these conditions, which supports and justifies our observations in (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Research into bone quality under the purview of reference 29 has demonstrated that bone metastasis from prostate and breast cancers significantly affects bone quality. This study identifies notable reductions in vertebral strength and stiffness under these conditions, which supports and justifies our observations in (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…The same group performed a higher resolution analysis at 6 um isometric voxel size, of 4 mm side cubes from vertebrae with PCBM obtained from two patients, and described a higher BV/TV, bone surface, trabecular number, trabecular connectivity, anisotropy and fractal dimensions in PCBM ( 10 ). More recently, mCT scanning at an isometric voxel size of 10.5 μm was used to analyzed 5 mm diameter cores obtained from cadaveric vertebra with metastasis from two men who died of PC, 3 patients who died of breast cancer and 3 from lung cancer ( 11 ). By complimenting this morphological analysis with mechanical testing and biochemical analysis, the PCBM cores were scored as sclerotic, lytic, or mixed, but for the statistical analysis, all samples were grouped according to imaging classification, thus no conclusion can be made from the specific cancer type.…”
Section: Discussionmentioning
confidence: 99%
“…Although informative, these are relatively low-resolution histologic descriptors, and only a handful of studies have ventured into high-resolution, or three-dimensional analysis of PCBMs. For instance, a series of synchrotron-based high-resolution micro-computer tomography (μCT) scans from two patient samples ( 9, 10 ), demonstrated alterations in bone mineral density and trabecular morphology and structure, and recently, a high-resolution μCT scan reported similar structural changes in PCBMs obtained from two patients ( 11 ). These highly relevant descriptions are limited by sample size, and they require further validation to draw definitive conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…With the development and advancement of various new anticancer drugs, next-generation sequencing, targeting, and immunotherapy, the treatment mode of patients with bone metastasis has gradually shifted to a chronic disease management mode. Long-term systemic follow-up and the continuous adjustment of drugs according to the patient's condition can confer long-term survival benefits, which is particularly important for improving tumor-bearing survival and QoL ( 6 ).…”
Section: Introductionmentioning
confidence: 99%